Perturbations of microRNA function in mouse dicer mutants produce retinal defects and lead to aberrant axon pathfinding at the optic chiasm. - Rita Pinter; Robert Hindges (PLoS ONE)
Background During development axons encounter a variety of choice points where they have to make appropriate pathfinding decisions. The optic chiasm is a major decision point for retinal ganglion cell (RGC) axons en route to their target in order to ensure the correct wiring of the visual system. MicroRNAs (miRNAs) belong to the class of small non-coding RNA molecules and have been identified as important regulators of a variety of processes during embryonic development. However, their involvement in axon guidance decisions is less clear. Methodology/principal findings We report here that the early loss of Dicer, an essential protein for the maturation of miRNAs, in all cells of the forming retina and optic chiasm leads to severe phenotypes of RGC axon pathfinding at the midline. Using a conditional deletion approach in mice, we find in homozygous Dicer mutants a marked increase of ipsilateral projections, RGC axons extending outside the optic chiasm, the formation of a secondary optic tract and a substantial number of RGC axons projecting aberrantly into the contralateral eye. In addition, the mutant mice display a microphthalmia phenotype. Conclusions Our work demonstrates an important role of Dicer controlling the extension of RGC axons to the brain proper. It indicates that miRNAs are essential regulatory elements for mechanisms that ensure correct axon guidance decisions at the midline and thus have a central function in the establishment of circuitry during the development of the nervous system.